Impact Of Nurse-Led Spiritual Care On Spiritual Well-Being Of Individuals With Respiratory Diseases: A Systematic Review - Navy Sealsi Adinda Prisca Marina; Yulis Setiya Dewi; Andri Setiya Wahyudi (Jurnal Ners, 2026)
Introduction: The management of critically ill respiratory patients in ICU’s necessitates a holistic approach incorporating spiritual care. While nurses occupy a strategic position to deliver spiritual interventions, implementation barriers persist due to the absence of standardized protocols. Systematic integration of spiritual dimensions into routine care protocols may significantly enhance both patient well-being and overall clinical outcomes. The aim of this study is to analyze the impact of nurse-led spiritual care on spiritual well-being of patients with respiratory diseases. Methods: A systematic review was conducted by 4 major database include Scopus, ProQuest, Science Direct and PubMed, for the last ten years publication 2015 to 2025 published in English. Egible studies included those that implemented of nurse led spiritual for individual with respiratory disease. Data extraction included study design, chacarteristic of participants and interventions, and measured outcome. Bias was assessed using the JBI Critical Appraisal Tools. Result: Nine studies (n = 9) scored by JBI critical appraisal from 77% to 92% included in the final analysis, involved 601 respondens from 7 countries, with duration of interventions ranging from 10 days to 24 weeks. The spiritual nursing care showed that nurse-delivered spiritual care interventions exert measurable positive effects on spiritual well-being among patients with respiratory diseases, with concomitant benefits observed across psychological and physiological health domains. Conclusion: The studied demonstrates that nurse-led spiritual care significantly improves spiritual well-being and related health outcomes in respiratory patients. The findings support integrating structured spiritual interventions into standard respiratory care, tailored to individual clinical and cultural needs. Future implementation requires both clinical guideline adoption and continued research to optimize long-term therapeutic benefits.